Anais Do XL Simpósio Brasileiro De Telecomunicações E Processamento De Sinais 2022
DOI: 10.14209/sbrt.2022.1570823103
|View full text |Cite
|
Sign up to set email alerts
|

Análise das Distribuições SαS e αSG na Modelagem do Ruído de Camarão-de-Estalo

Abstract: Resumo-Sistemas de comunicação subaquáticos por ondas acústicas estão sujeitos à degradação de desempenho causada pelo ruído impulsivo gerado pelo crustáceo camarão-de-estalo. Em análises matemáticas ou simulações, esse ruído é comumente modelado por meio de amostras temporalmente descorrelacionadas seguindo a distribuição alfa-estável simétrica (symmetric alpha-stable, SαS). Neste artigo analisa-se a adequação dessa distribuição em contraste com a distribuição alfa-sub-Gaussiana (alpha-sub-Gaussian, αSG) com … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
(19 reference statements)
1
3
0
Order By: Relevance
“…Conventional and DCR-based receiver models are used to compare the performances of the energy detector (ED), the absolute value cumulating (AVC) detector, the Gerschgorin radii and centers ratio (GRCR) detector, the Gini index detector (GID), the Pietra-Ricci index detector (PRIDe) and the locally most powerful invariant test (LMPIT) detector. This work merges and extends the research reported in [17] and [27]. The merged part refers to the assessment of the conventional and the DCR-based receiver models under SαS and αSG noise.…”
Section: B Contributions and Organization Of The Articlesupporting
confidence: 59%
See 3 more Smart Citations
“…Conventional and DCR-based receiver models are used to compare the performances of the energy detector (ED), the absolute value cumulating (AVC) detector, the Gerschgorin radii and centers ratio (GRCR) detector, the Gini index detector (GID), the Pietra-Ricci index detector (PRIDe) and the locally most powerful invariant test (LMPIT) detector. This work merges and extends the research reported in [17] and [27]. The merged part refers to the assessment of the conventional and the DCR-based receiver models under SαS and αSG noise.…”
Section: B Contributions and Organization Of The Articlesupporting
confidence: 59%
“…References [20]- [25] are cited as examples. In [17], the adequacy of the SαS distribution is analyzed in contrast to the αSG distribution with non-zero temporal correlation, in the context of underwater spectrum sensing subjected to snapping shrimp noise.…”
Section: A Related Researchmentioning
confidence: 99%
See 2 more Smart Citations